Dispositivos móveis no ensino-aprendizagem de áreas e volumes - Silva, Cristhiane Ferreira Almeida da (2017)
This research is part of the line of Educational Technology Management Network of the Graduate Programme Professional Masters in Educational Technology Network. This work aims to contribute to improving the understanding of the content of areas and volumes through Digital Educational Resources operationalized in mobile devices. Didactic sequences were developed in order to analyze the evolution of the students' comprehension in the content of Geometry, where the specific objectives are: 1) to map open educational resources involving geometry, available in public portals that can be operated in mobile devices; 2) to plan activities through mobile devices, about the content of plane geometry, focusing on measurements and magnitudes, from national evaluation questions; 3) implement activities with educational resources, available in public portals, using mobile devices in collaborative teaching-learning Mathematics. The methodology used in the study was action research where data were collected through observations, document analysis and audio recordings. As a result, the implementation of digital educational resources in mobile devices in the issues addressed by the project activities has contributed to the improvement in student learning development, through activities that integrate the TER. It was observed that the students had improved performance in the realization of the questions with the contribution of digital resources through mobile devices, and with this, the result was satisfactory.